Can Arthrogenic Muscle Inhibition Exist in Peroneal Muscles Among People with Chronic Ankle Instability? A Cross-sectional Study - Shiyu Dong; Yanhao Liu; Ziyin Liu; Peixin Shen; Hao Sun; Ping Zhang; Daniel T.P. Fong; Qipeng Song (SpringerOpen, 2024)
Abstract Background Ankle sprains lead to an unexplained reduction of ankle eversion strength, and arthrogenic muscle inhibition (AMI) in peroneal muscles is considered one of the underlying causes. This study aimed to observe the presence of AMI in peroneal muscles among people with chronic ankle instability (CAI). Methods Sixty-three people with CAI and another sixty-three without CAI conducted maximal voluntary isometric contraction (MVIC) and superimposed burst (SIB) tests during ankle eversion, then fifteen people with CAI and fifteen without CAI were randomly invited to repeat the same tests to calculate the test-retest reliability. Electrical stimulation was applied to the peroneal muscles while the participants were performing MVIC, and the central activation ratio (CAR) was obtained by dividing MVIC torque by the sum of MVIC and SIB torques, representing the degree of AMI. Results The intra-class correlation coefficients were 0.77 (0.45-0.92) and 0.92 (0.79-0.97) for the affected and unaffected limbs among people with CAI, and 0.97 (0.91-0.99) and 0.93 (0.82-0.97) for the controlled affected and unaffected limbs among people without CAI; Significant group × limb interaction was detected in the peroneal CAR (p = 0.008). The CARs were lower among people with CAI in the affected and unaffected limbs, compared with those without CAI (affected limb = 82.54 ± 9.46%, controlled affected limb = 94.64 ± 6.37%, p < 0.001; unaffected limb = 89.21 ± 8.04%, controlled unaffected limb = 94.93 ± 6.01%, p = 0.016). The CARs in the affected limbs were lower than those in the unaffected limbs among people with CAI (p = 0.023). No differences between limbs were found for CAR in the people without CAI (p = 0.10). Conclusions Bilateral AMI of peroneal muscles is observed among people with CAI. Their affected limbs have higher levels of AMI than the unaffected limbs.